Advancing MSME Digitalization through Community-Based Digital Platform Training in Bangun Jiwo Barat - Dimas Bagus Wiranatakusuma; Fawwaz Ardhan Kencana; Satria Utama (CV. Era Digital Nusantara, 2026)
Micro, small, and medium enterprises (MSMEs) represent the backbone of Indonesia's local economy, yet their participation in digital platform ecosystems remains constrained by limited digital literacy, infrastructure, and institutional support. This study employs a Systematic Literature Review (SLR) of 20 Scopus-indexed articles to examine how community-based digital platform training can accelerate MSME digitalization, focusing on Bangun Jiwo Barat, Bantul, Yogyakarta. Guided by the PRISMA framework and supported by VOSviewer bibliometric analysis, the study identifies four dominant themes: digital literacy, e-commerce adoption, supply chain integration, and community empowerment. Density visualization highlights commerce and information systems as the most intensively studied topics, while overlay visualization identifies artificial intelligence, blockchain, and data marketplaces as emerging research trends during 2024–2025. As part of the community service program, HALVORA (Halal Verification Retail Online Apps) was introduced as a practical learning platform integrating halal verification, digital marketing, business networking, and fintech-enabled services. The platform enabled participants to gain hands-on experience in promoting products, expanding market access, and strengthening entrepreneurial capabilities through digital technology. Survey results from the Bangun Jiwo Barat community indicate that 82.5% of participants were familiar with digital marketplace platforms, although most had limited experience utilizing them for business development. The findings demonstrate that effective digital empowerment requires combining practical digital platform training, financial literacy, and continuous mentoring. Furthermore, HALVORA has the potential to serve not only as a digital marketplace but also as a community empowerment instrument that enhances digital literacy, supports MSME business expansion, and promotes sustainable local economic development. The study recommends stronger collaboration among local governments, universities, community organizations, and technology providers to build an inclusive and sustainable digital ecosystem for MSMEs.